2004
DOI: 10.1081/scc-120027244
|View full text |Cite
|
Sign up to set email alerts
|

New Straightforward Quinoline Synthesis from the Mannich Reaction of α‐Ketohydrazones

Abstract: The addition of a-ketohydrazones to 2-acetamidobenzaldehyde proceeds efficiently in the presence of N-benzylpiperazine to afford in good to high yields the expected Mannich adducts; these are easily converted to quinoline derivatives under acidic conditions in a new Azo-Friedländer reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Under these conditions, deprotection, cyclization, and elimination of the N-benzyl piperazine took place in a single step giving the 2,3-disubstituted quinoline (eq 14). 71 N-Acetylated 2-amino benzaldehydes have been combined with amides to give 2-amino-3-hydroxy quinoline derivatives in moderate yields. 72 The base-catalyzed intramolecular condensation of 2-acetamido aceto or benzophenones is known as the Camps quinoline synthesis.…”
Section: The 2-amino Carbonyl Componentmentioning
confidence: 99%
See 3 more Smart Citations
“…Under these conditions, deprotection, cyclization, and elimination of the N-benzyl piperazine took place in a single step giving the 2,3-disubstituted quinoline (eq 14). 71 N-Acetylated 2-amino benzaldehydes have been combined with amides to give 2-amino-3-hydroxy quinoline derivatives in moderate yields. 72 The base-catalyzed intramolecular condensation of 2-acetamido aceto or benzophenones is known as the Camps quinoline synthesis.…”
Section: The 2-amino Carbonyl Componentmentioning
confidence: 99%
“…82 The use of R-ketohydrazones, which are essentially azosubstituted ketones, has been already discussed in the context of an azo-Friedla ¨nder reaction based on the reaction with 2-acetamido benzaldehyde derivatives (eq 14). 71 A major limitation of the Friedla ¨nder reaction is the lack of regioselectivity when using unsymmetrical ketones. For example, it has been observed that the usual base-catalyzed Friedla ¨nder reaction conditions employing 2-amino nicotinaldehyde and 2-alkanones, such as 2-pentanone, give roughly a 1:2 mixture of 2-monosubstituted 1,8-naphthyridines (15) to 2,3-disubstituted ones (16) (Scheme 4).…”
Section: The Active Methylene Componentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, the literature describes that aldehydic arylhydrazones can be considered enamine analogues and that they, in appropriate conditions, promote the formation of arylazo compounds, only a few examples of these compounds are reported. , Recently, L. El Kaïm et al have reported the synthesis of several heterocyclic compounds via unstable azoalkenes trapped in situ by various nucleophiles …”
Section: Resultsmentioning
confidence: 99%